G258 Epilepsy in western uganda: using satellite clinics to remove barriers to seeking care. (12th March 2018) - Harris, C; George, B; Harris, U; Munyagwa, M; Greenough, A
Abstract : Aims: Epilepsy affects three times as many children in African countries compared to higher income settings. Unfortunately, epilepsy clinics in Africa countries are poorly attended even when there is free provision of care. To reduce this treatment gap we introduced low cost rural epilepsy clinics in Western Uganda. The aim of this study was to evaluate their effectiveness. Methods: Pre-intervention attendance and follow-up at hospital based clinics was audited for three month periods. The intervention involved a new guideline written by the medical, pharmaceutical and community rehabilitation staff at the regional hospital, providing information about the locally available medications, how to start medication and monitor side effects. In addition, clinics local to the hospital were introduced and then satellite clinics in four rural locations were introduced. The cost of these extra clinics, attendance and follow-up at the clinics were audited over nine months post intervention and re-audited six years after the intervention. Cost analyses excluded medication costs as medications were provided by the government to the hospital and community clinics without charge. Clinic costs did not change depending on patient attendance. Results: One patient attended the hospital clinic each month. Post intervention, at the clinics local to the hospital a median of 8 patients (range 2–12) attended per month with 100% attending for follow up at the booked time; the cost per clinic was £15. At the satellite rural clinics, there was a median of 42 (range 15 to 56) patients per clinic with 70% of patients attending follow up appointments; the cost per clinic was £34. The hospital based clinic ceased to exist. Six years post intervention the attendance at the satellite clinics was a median of 47 patients (range 25 to 85) per clinic; the cost per clinic remained £34. Satellite clinic attendance post intervention was significantly higher than locally held clinics (p=0.004). Conclusion: Rural epilepsy clinics away from the hospital were associated with higher attendance which was sustained six years post intervention. This was achieved at relatively low cost.